Non-monetary factors were an important driver of residential energy savings during the energy crisis - Sophie M. Behr; Till Köveker (DIW Weekly Report, 2025)
The Russian invasion of Ukraine in 2022 triggered an energy crisis in Germany, with consumer energy prices skyrocketing over the course of the year. Due to concerns about gas shortages, various programs aimed at reducing consumption were set up and the German Federal Government and numerous organizations appealed to consumers to save as much energy as possible. This Weekly Report investigates how much of the energy savings of private households (16 percent in total) was due to higher prices and how much was due to non-monetary factors, such as government appeals, public campaigns, or a fear of price increases. The results of an analysis of a comprehensive dataset on the prices and consumption of heating energy in multi-family buildings in Germany show that only about two percentage points of savings were due to higher prices. Therefore, non-monetary factors had a nearly four times greater effect on heating energy consumption at over eight percentage points, at least in the short term. The rest of the savings is due to factors such as weather. To tackle future energy crises in the short term, policymakers should utilize non-price interventions to complement the limited effect of heating energy price increases on savings.
Keywords: Q41; Q48; 330; Energy crisis; Energy policy; Causal inference; Price elasticity